PERAN GURU DALAM MEMBINA PERKEMBANGAN BAHASA ANAK KELOMPOK B DI TK CUT MEUTIA BANDA ACEH - Erfinawati; Ismawirna (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2019)
The role of the teacher is very important in the development of the language of children in school, especially in children aged 5 years because that age children are developing so that it requires a good, motivating and teaching facilitator. Data is collected through observation, and interviews. The subjects in this study were teachers and 5-year-old children in group B TK Cut Meutia Banda Aceh. The data analysis technique in this study uses qualitative and draw conclusions. The role of the teacher as a motivator in the development of the language of 5-year-old children at TK Cut Meutia in Banda Aceh is good. That is, most of the Kindergarten Cut Meutia teachers can carry out their role as motivators in developing children's language which motivates children to improve their language development, encourages children to develop language skills, provides rewards to support children's language skills. The role of the teacher as a mediator in the development of the oral language of 5-yearold children at TK Cut Meutia in Banda Aceh is good. This means that most of the TK Cut Meutia Banda Aceh Kindergarten teachers in Banda Aceh can carry out their role as mediators in developing children's language, namely providing stimuli in children's language development, applying various approaches, strategies, methods that suit the needs of early childhood. The role of the teacher as a facilitator in the development of the oral language of 5-year-old children at TK Cut Meutia in Banda Aceh is moderate / good. This means that the teacher is able to provide learning media that are able to stimulate the cognitive of children, giving children the attraction so that children are interested in participating in learning. The teacher is not only a motivator, mediator, and facilitator, but also trains children to recite a few words correctly and correctly, arranges simple instructions creatively in presenting media so that children respond well to the information conveyed. AbstrakPeran guru merupakan hal yang sangat penting dalam tumbuh kembang bahasa anak di sekolah terutama pada anak usia 5 tahun karana usia tersebut anak sedang berkembang sehingga membutukan fasilator yang baik, memotivasi, dan mengajar. Data dikumpulkan melalui observasi, dan wawancara. Subjek dalam penelitian ini adalah guru dan anak usia 5 tahun kelompok B TK Cut Meutia Banda Aceh. Teknik analisis data dalam penelitian ini menggunakan kualitatif dan menarik kesimpulan. Peran guru sebagai motivator dalam pengembangan bahasa anak usia 5 tahan di TK Cut Meutia Banda Aceh adalah baik. Artinya, sebagian besar guru TK Cut Meutia dapat melaksanakan perananya sebagai motivator dalam mengembangkan bahasa anak yaitu memotifasi anak untuk meningkatkan perkembangan bahasanya, mendorong anak untuk mengembangkan kemampuan berbahasa, memberikan reward untuk menunjang kemampuan berbahasaanak. Peran guru sebagai mediator dalam pengembangan bahasa lisan anak usia 5 tahun di TK Cut Meutia Banda Aceh adalah baik. Artinya, sebagian besar guru TK Cut Meutia Banda Aceh dapat melaksanakan perananya sebagai mediator dalam mengembangkan bahasa anak yaitu memberikan stimulus dalam perkembangan bahasa anak, menerapkan berbagai pendektan, strategi, metode yang sesuai kebutuhan anak usia dini. Peran guru sebagai fasilitator dalam pengembangan bahasa lisan anak usia 5 tahun di TK Cut Meutia Banda Aceh adalah sedang/baik. Artinya guru mampu menyediakan media pembelajaryang mampu merangsang kognitif anak, memberi daya tarik anak sehingga anak tertarik dalam mengikuti pembelajaran. Guru tidak hanya menjadi motivator, mediator, dan fasilitor tetapi juga melatih anak dalam melafalkan beberapa kata dengan tepat dan benar, menyusun kalinat sederhana dengan kreatif dalam menghadirkan media sehingga anak merespon baik terhadap informasi yang disampaikan. Kata Kunci: Peran, Guru, Perkembangan, Bahasa, Anak, 5 Tahun